PENGARUH MATA KULIAH PERENCANAAN PENGAJARAN FISIKA TERHADAP MATA KULIAH PENGAJARAN MIKRO PADA MAHASISWA PENDIDIKAN FISIKA FKIP UNSYIAH TAHUN 2016/2017 - Iqbal Sugita; Elisa Kasli; susanna Susanna (FKIP Unsyiah, 2017)
The problem of this study does the subject of physics teaching plan influence micro-teaching for physics student academic year 2016/2017 faculty of education and teaching unsyiah ? the objective of this study is to recognizing, the influence of the subject physics teaching plan toward micro-teaching conducted by physics students FKIP Unsyiah academic year 2016/2017. The population of this study is the students at study program of physics FKIP Unsyiah year 2016-2017 who are conducting micro-teaching practice and have passed the subject physics teaching practice. The technique of date collection used observation and documentation study while the technique of date analysis formula from this study the regearcher found thitung ttable (2.56 1.7). This result means that there is an influence of the subject physics teaching plan toward micro-teaching practice done by the students of study program of physics FKIP Unsyiah year 2017. It is recommended that the students in micro-teaching should obtain a deeper understanding on the materials in the subject physics teaching plan.